2009
DOI: 10.1097/mao.0b013e3181b4eebf
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Effectiveness of Stapes Surgery for Otosclerosis in a Multicenter Audit Setting

Abstract: Results of hearing outcome are similar to previous, primarily retrospective, single-center studies. Our data confirm the effectiveness of stapes surgery in patients with otosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 14 publications
1
45
1
3
Order By: Relevance
“…The majority of our study patients (218/239, 91.2 %) reported being right handed, a finding in agreement with the studies on hand preferences in different populations [18][19][20][21]28]. Our findings on female prevalence among the patients with otosclerosis, mean age at presentation for stapes surgery and gender differences in handedness were consistent with those in the literature [2,3,[8][9][10][11][28][29][30][31].…”
Section: Discussionsupporting
confidence: 95%
“…The majority of our study patients (218/239, 91.2 %) reported being right handed, a finding in agreement with the studies on hand preferences in different populations [18][19][20][21]28]. Our findings on female prevalence among the patients with otosclerosis, mean age at presentation for stapes surgery and gender differences in handedness were consistent with those in the literature [2,3,[8][9][10][11][28][29][30][31].…”
Section: Discussionsupporting
confidence: 95%
“…G1 is the Nitinol group, and G2 is the manually crimping group, if present. Van Rompaey et al (20) did not report a direct comparison between Nitinol and manually crimping prostheses in their 2009 article but reported this comparison in an abstract in early 2010 (21). These studies were combined.…”
Section: Qualitative and Quantitative Data Synthesismentioning
confidence: 96%
“…One study demonstrated a statistically significant difference at 3 months favoring the manually crimping group (20,21). All other included studies could not demonstrate superiority of any prosthesis type.…”
Section: Qualitative and Quantitative Data Synthesismentioning
confidence: 97%
See 2 more Smart Citations